Pemanfaatan Aplikasi e-office dalam Manajemen Arsip di Madrasah Aliyah Negeri 4 Kota Pekanbaru - Dianita, Endang (MAN 4 Kota Pekanbaru, 2022)
The rapid development of technology in the industrial revolution 4.0 is marked by the presence of electronic devices that humans can utilize as users in various work activities. Facing this phenomenon, e-office as records management needs serious attention. In addition to time efficiency, the use of technology can also reduce costs and other resources such as paper, ink, etc. Unfortunately, users sometimes lack the skills to use existing electronic systems. Therefore, this article aims to explain the use of e-office in MAN 4 Kota Pekanbaru and the opportunities, challenges, and obstacles faced. This article was written with a case study approach, namely by explaining the facts in the field using a qualitative descriptive method. The study's conclusion shows that archive management at MAN 4 Kota Pekanbaru is currently carried out using manual and online systems. However, there were several challenges and obstacles encountered during the study, so it is recommended to conduct training so that HR skills can be adequately improved and e-office applications can be implemented optimally.